Gaya Kepemimpinan Kelembagaan di Era Disrupsi (Tinjauan dari Perspektif Manajemen) - Keristian Dahurandi (Jurnal Alternatif Wacana Ilmiah Interkultural, 2020)
The Disruption era is part of the context of today’s society. This era was born from revolution 4.0. The era of revolution 4.0 is one stage of the industrial revolution that adopts the idea of a computerized system in management. By doing so, various virtual information technology products have emerged that lead to MOOCs (Massive Open Online Courses) system. The flood of technological innovations certainly brings various dilemma situations in various dimensions of human life. This situation arises when something common becomes unusual or vice versa thanks to the ability of digital technology. One of the permanent life systems and functions which regulates human efforts to meet their daily needs is institutions both local institutions such as families and indigenous peoples and new institutions (such as modern organizations). One of the important institutional actors is leadership. In short, leadership is defined as a leader’s efforts to influence its members to achieve goals. Therefore, it requires at least three fundamental institutional leadership styles to face the disruption era, namely situational leadership, transformational leadership and servant leadership. Situational leadership helps leaders to strengthen internally human resource commitment of staff or institutional members in accordance with the institutional context. Transformational leadership encourages the creation of institutional innovation according to its vision and mission. Institutional innovation begins with a leader’s efforts to constantly renew himself (on going formation) so that he/she is able to become agents of change for the institution and its members. Finally, servant leadership tries to encourage institutional functions to remain human-oriented since human beings are the image of God/Creator. These three leadership styles should become standard leadership styles which should be applied in institutions to ward off the dilemma of innovation in the disruption era.